The Impact of Confidence on Revisit Intentions to the Upper Northern Region Amid PM 2.5 Particulate Pollution - Mouckrong, Ratchatorn; Boonmeesrisanga, Manassinee; Taweephol, Rachanon (Journal of Rattana Bundit University, 2025)
This study aimed to 1) examine the level of confidence and revisit intention among Thai tourists who traveled to the upper northern region of Thailand during periods of PM 2.5 particulate pollution, and 2) analyze the influence of confidence on their revisit intention under such conditions. The sample comprised 400 Thai tourists with prior travel experience in the region during PM 2.5 pollution episodes. Data were analyzed using percentages, means, standard deviations, Pearson’s correlation coefficient, and multiple regression analysis. The findings revealed that: 1) when classified by aspect, the level of confidence was highest in the social aspect, followed by the environmental, economic, and governmental management aspects. The overall level of revisit intention was high. 2) Confidence in the public administration and social aspects significantly influenced tourists’ intention to revisit the upper northern region for tourism during periods of PM 2.5 particulate pollution.